(3GdGSJjYGHs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdCUHgGfi bGd cJH Edi CHh YeQGf ehSi GdTGWHi , bGd (B: (3MQa GdLje , HGH LYaQ Hf CHj WGdH s
(3BNQgG (B:s
(3Je GdSaQ GdKGfi ef cJGH GdGSJjYGH jJdhg Ef TGA Gddg ai Chd GdKGdK RjO Hf GdNWGH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI (B((3efWb (B95) s
Keywords: (3GdadSaI hGdefWbs